The effect of leech extracts on endothelial cell coagulation-related factors and endothelial dysfuction-related molecules. (3rd April 2019) - Xu, Lixu; Li, Xue; Zhang, E; Liang, Hao; Li, Weiting; Wang, Shangyi; Song, Shuliang; Ji, Aiguo
ABSTRACT: Objective : This study was focused on screening leech extracts to identify those with little or no anti-coagulation effect or with significant anti-endothelial dysfunction activity. Methods : Different leech extracts were prepared by enzymolysis and microbial transformation and their cytotoxicity were measured by MTT assay. The effect of different leech extracts on mRNA expression of coagulation-related factors (PAI, vWF, tPA, PS, TFPI, TM) was quantified by RT-PCR. After identifying a leech extract with little anti-coagulatory effect, RT-PCR was then used to assess the effect of this extract on the mRNA expression of endothelial dysfunction-related molecules (ET-1, iNOS, MCP-1, IL-6). Results : 8 leech extracts were obtained, including 4 enzymatic extracts (LP, PHL, PTHL, CEHL) and 4 Lactobacillus metabolites (MRS, MRS-1, MRS-2, and MRS-3). Following optimization of conditions using MTT assays, we treated EA.hy926 cells with 0, 12.5, 25, 50 μg/mL of LP, PTHL, CEHL, MRS, MRS-1 or MRS-3 extract for 24 h. We found that PHL and MRS-1 had no significant effect on coagulation-related factors. Furthermore, treatment with 50 μg/mL PHL resulted in significant decreases in ET-1, iNOS, MCP-1, and IL-6 mRNA expression by 28.06%, 33.30%, 19.80%, and 52.34%, respectively. Conclusions : In the present study, we found that PHL, a pepsin hydrolysate of leech with little anti-coagulatory effect, could significantly suppress TNF-α induced mRNA overexpression of endothelial dysfunction-related molecules (ET-1, iNOS, MCP-1, and IL-6). These results provide a reliable experimental basis for identifying new anti-atherosclerosis therapeutics for long term use and with minimal bleeding side effects.